SISTEM PENCAMPURAN CAT MENGGUNAKAN MIKROKONTROLER DENGAN INTERFACE PC - Evana, Yoseph; Indriaty, Fany; Hugeng, Hugeng (TESLA Jurnal Teknik Elektro UNTAR, 2008)
The design of automatic system paint mixer is design to make process of mixing easier, it is depend on colour input and colour volume from user which using Personal Computer. The design is make for mixing the paint in short time and have accuracy in the result colour and in the operational do not need an expert who understand how to mix paint. This device is using microcontroller which is controlling the solenoid valve, stand mixer, and any other support hardware. Besides that, the device is using colour sensor to check the result is match with input from user or not, if not match then the microcontroller will re-calibrate the data from colour sensor.